OPERATION MANAGEMENT IN J&T EXPRESS - Nor Athierah bt Zainon; Angel Oon; Stefanus Rumangkit (Proceeding International Conference on Information Technology and Business, 2018)
JT Express is an express delivery company that applies technology development as the basic system. Extensive network that JT Express facilitates express services for customers throughout Indonesia. JT Express serve the delivery within city, inter-city, inter-provincial, and also e-commerce customer. JT Express provides pick up service with high transmission speed, at the same time also support the growth of e-commerce business. JT Express in operation management provide the good services to customers for had good time e-shopping and quality goods cooperate with some companies like Tokopedia, Shopee and Bukalapak and etc. JT Express always improve their services by used the new technologies as like AI system for control the shipping of goods and also social media as like Facebook, WeChat, Twitter, Instagram, Line and YouTube for connected with customers and always upload new information at there. So that JT Express management can know the need of demand form customers commitment it with their customer service can improve their level of services.Keywords: JT Express; Shipping; Operation Management;